The Impact of Income Tax Over Financial Performance of Companies Listed on The Bucharest Stock Exchange - Aurelia Ștefănescu; Ileana Cosmina Pitulice; Viorica Georgiana Mînzu (Journal of Accounting and Management Information Systems (JAMIS), 2018)
By its multiple facets, income tax is a subject of great interest both for academic and professional environment, on a microeconomic and macroeconomic level. After analyzing the relevant literature in the field, in order to demonstrate the influence of income tax over a company's performance, two econometric models were designed, having as dependent variables return on equity and net profit's margin rate. For applying multiple regressions we used a sample of companies listed on Bucharest Stock Exchange and the analysed indicators were extracted from their annual financial statements. Econometric modelling used for return on equity and net profit's margin demonstrated that effective tax rate influences in a negative way a company's financial performance. Limits of research have been evidenced as being methodological, such as the small size of the sample.
Keywords: M41; C58; G31; M10; H32; 650; empirical research; income tax; financial performance; listed companies; Romania